DEVELOPING AN ENGLISH "FRONT OFFICE" SUPPLEMENTARY BOOK FOR HOSPITALITY MAJORS AT SMKN 3 KOTA BLITAR - Ayu Hartina Sari; Istina Atul Makrifah; Tyas Alhim Mubarok (PROJECT (Professional Journal of English Education), 2023)
The aim of this study was to develop a supplementary book "Front Office" in English for hospitality majors at SMKN 3 Kota Blitar. The reason behind the development of this product is that English is very important, especially for communicating with guests at the hotel's front office. What is learned in the existing departmental modules is in the form of rules for working in the front office, the application of communication in English that is presented is still limited. In addition, demonstrations conducted by teachers also have limitations. They can not be repeated to meet the needs of students in practice. This research is to develop a supplementary book using ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through questionnaires and interviews. Questionnaires were distributed to 30 students majoring in hospitality at SMKN 3 Kota Blitar. Meanwhile, interviews were conducted with teachers and several major students. The findings show that students' evaluations on the results of the subject supplementary books received positive feedback and their responses were mostly "Very Good". They said that the material helped them understand certain conversations according to the front office role of the hospitality major (100%). There are suggestions about the balance of the questionnaire, namely about the appearance of products that are less attractive to students (66.7%) and the presentation of letter variants that still need to be improved (63.3%). Keywords:  Supplementary Book; Front Office; Materials Development